Recovery from impaired working memory performance during chronic Δ-9-tetrahydrocannabinol administration to adolescent rhesus monkeys. (February 2020) - Verrico, Christopher D; Mathai, David S; Gu, Hong; Sampson, Allan R; Lewis, David A
Background: The relationship between adolescent cannabis use and susceptibility to persistent cognitive impairments is poorly understood. Aims: We examined the effects of repeated exposure to Δ-9-tetrahydrocannabinol (THC) on reinforcement-related learning and performance of spatial working memory (WM) tasks of varying difficulty in adolescent monkeys. Methods: Seven pairs of male adolescent rhesus monkeys, matched for baseline cognitive performance, received vehicle or THC intravenously 5 days/week for 12 months. Performance on 4-item spatial WM trials was assessed throughout the 12-month study period. At the 6-month time point, more difficult novel and distractor 8-item spatial WM trials were added. Residual effects on performance were determined 23 or 71 h after THC or vehicle administration throughout the study. Results/outcomes: Relative to vehicle-exposed animals, repeated THC exposure was initially associated with significantly slower improvement in performance accuracy on 4-item spatial WM trials; however, this performance difference gradually diminished such that by month 12, accuracy did not significantly differ between vehicle and THC groups. Similarly, for the novel and distractor 8-item trials introduced at month 6, performance accuracy improved more slowly in the THC than in the vehicle group, despite comparable performance between groups on the 4-item task during this same period. Conclusions/interpretation: These findings suggest that compared to vehicle exposure, THC exposure during adolescence impairs the reinforcement-related learning process required for improved performance on spatial WM tasks, but this impairment might be overcome with continued training, even in the face of ongoing THC exposure.